2022
DOI: 10.1155/2022/5361241
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Sensitizes Pancreatic Cancer Cells to Erastin-Induced Ferroptosis by Activating the AMPK/Nrf2/HMOX1 Pathway

Abstract: Ferroptosis is a type of regulated cell death that displays a promising therapeutic pathway for drug-resistant tumor cells. However, some pancreatic cancer (PC) cells are less sensitive to erastin-induced ferroptosis, and normal pancreatic cells are susceptible to this newly discovered cell death. Therefore, there is an urgent need to find drugs to enhance the sensitivity of these PC cells to erastin while limiting side effects. Here, we found that the oxidized form of vitamin C-dehydroascorbic acid (DHA) can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In the BC panel, GSTK1, which is an antioxidant contained in peroxisomes, correlated with low VitC sensitivity, and has been found to be involved in ferroptosis together with CAT, SOD1 and PRDX5(74). This cancer cell death process has been linked to VitC anti-cancer effect in several recent studies and may be further studied(75,76).…”
Section: Discussionmentioning
confidence: 99%
“…In the BC panel, GSTK1, which is an antioxidant contained in peroxisomes, correlated with low VitC sensitivity, and has been found to be involved in ferroptosis together with CAT, SOD1 and PRDX5(74). This cancer cell death process has been linked to VitC anti-cancer effect in several recent studies and may be further studied(75,76).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, natural products such as vitamins, coumarins, and unsaturated fatty acids are considered potential ferroptosis inducers in cancer cells (Y. Liu, Huang, et al, 2022; Vermonden et al, 2021; Xiu et al, 2023). Vitamin C increased intracellular iron levels by promoting ferritin degradation (X. Wang, Xu, et al, 2021).…”
Section: Regulation Of Ferroptosis By Natural Productsmentioning
confidence: 99%
“…Nevertheless, Wang et al were able to demonstrate the induction of ferroptosis by high-dose ascorbate in anaplastic thyroid cancer cells [ 80 ]. Furthermore, it could be shown that ascorbate-induced accumulation of iron in combination with a simultaneous GSH reduction resulted in the enhancement of erastin-induced ferroptosis in pancreatic cancer cells [ 81 ].…”
Section: Generation Of Reactive Oxygen Species and Intracellular Toxi...mentioning
confidence: 99%